Heat acclimation--mechanisms of adaptation to exercise in the heat - Nielsen, B. (International Journal of Sports Medicine, 1998)
Repeated exposures to exercise and heat produce acclimatization, changes in physiological function by which the tolerance to heat stress is improved. The main issues to be discussed are the possible mechanisms for the increase in plasma volume, the increase in sweating rate and the endocrine responses to exercise with acclimation to both dry and humid heat. This will be discussed on the basis of the literature and our recent and ongoing experiments. We have tried to analyze this by comparing different acclimation procedures: exercise at 50-60% V/O2max, 60-90 min, dry heat 40 degrees C, 20% RH; 40-50% VO2max, 45-51 min, humid heat 35 degrees C, 85% RH; and 70-75% VO2max, 30-35 min, dry heat 40 degrees C, 20% RH. Subjects exercised in dry or humid heat for 8-12 consecutive days. Acclimation was achieved by all procedures, as indicated by a lower heart rate, increased plasma volume and sweating rate. We hypothesize that it is the repeated exposures to high core temperature that induce the changes, possibly via endocrine factors activated by the rising core temperature and the prolonged exercise. The increased sensitivity of the sweat glands for thermal and hormonal stimuli after acclimation may be obtained through an increase in receptor density for neural and humoral stimuli, an increase in the size, or, in number of active sweat glands.